2018
DOI: 10.1111/xen.12465
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac xenografts show reduced survival in the absence of transgenic human thrombomodulin expression in donor pigs

Abstract: A combination of genetic manipulations of donor organs and target‐specific immunosuppression is instrumental in achieving long‐term cardiac xenograft survival. Recently, results from our preclinical pig‐to‐baboon heterotopic cardiac xenotransplantation model suggest that a three‐pronged approach is successful in extending xenograft survival: (a) α‐1,3‐galactosyl transferase (Gal) gene knockout in donor pigs (GTKO) to prevent Gal‐specific antibody‐mediated rejection; (b) transgenic expression of human complemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 37 publications
1
36
0
Order By: Relevance
“…11 However, coagulation pathway dysregulation occurs commonly in both the xenograft recipient (consumptive coagulopathy, thrombocytopenia) and xenograft (thrombotic microangiopathy) despite the combined GTKO and CD46 modifications, and even when pharmacologic control of both cellular and humoral rejection is apparently efficient, as reflected by absence of detectable T-cell graft infiltration or elicited anti-pig antibody. 11 As first reported by us 3 and recently by others, 12 the current report confirmed that expression of hTBM in GTKO.hCD46 hearts coupled with an anti-CD40/CD154-based immunosuppressive regimen and heparin anticoagulation consistently prevented coagulation pathway dysregulation in baboons. Whether this result can be achieved exclusively using clinically approved immunosuppressants 13 instead of currently unapproved costimulation pathway blockers is an important remaining question of practical importance to obtaining regulatory approval for a proposed pharmacologic ''cocktail'' to be tested in the first clinical trial.…”
supporting
confidence: 89%
“…11 However, coagulation pathway dysregulation occurs commonly in both the xenograft recipient (consumptive coagulopathy, thrombocytopenia) and xenograft (thrombotic microangiopathy) despite the combined GTKO and CD46 modifications, and even when pharmacologic control of both cellular and humoral rejection is apparently efficient, as reflected by absence of detectable T-cell graft infiltration or elicited anti-pig antibody. 11 As first reported by us 3 and recently by others, 12 the current report confirmed that expression of hTBM in GTKO.hCD46 hearts coupled with an anti-CD40/CD154-based immunosuppressive regimen and heparin anticoagulation consistently prevented coagulation pathway dysregulation in baboons. Whether this result can be achieved exclusively using clinically approved immunosuppressants 13 instead of currently unapproved costimulation pathway blockers is an important remaining question of practical importance to obtaining regulatory approval for a proposed pharmacologic ''cocktail'' to be tested in the first clinical trial.…”
supporting
confidence: 89%
“…In animal studies, hTBM is often used as one of multiple transgenes . Therefore, it is difficult to rule out the effect of hTBM alone in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…While immunosuppression without hTBM appeared quite effective, TMA was still present in these animals. In contrast, additional expression of hTBM lead to better survival and could prevent TMA, underlining the importance for clinical xenotransplantation . The longest survival after cardiac xenotransplantation could be achieved only with triple‐transgenic animals expressing hTBM in combination with GTKO and hCD46 .…”
Section: Discussionmentioning
confidence: 99%
“…Pig aortic endothelial cells expressing hTBM were reported to substantially suppress prothrombinase activity, delay human plasma clotting time, and exhibit less activity in inducing human platelet aggregation (143,144). In the pig-to-baboon model, hTBM expression on cardiac xenografts confers an independent protective effect for prolonging graft survival time (145,146). Another key player in the anticoagulation system is EPCR, which also mediates anti-inflammatory and cytoprotective signaling (147).…”
Section: Expression Of Human Coagulation Regulation Proteinsmentioning
confidence: 99%